ChemInform Abstract: Utilization of Alkoxysilyl Groups for the Creation of Structurally Controlled Siloxane‐Based Nanomaterials. Issue 9 (4th March 2014) - Kuroda, Kazuyuki; Shimojima, Atsushi; Kawahara, Kazufumi; Wakabayashi, Ryutaro; Tamura, Yasuhiro; Asakura, Yusuke; Kitahara, Masaki
Abstract Review: 73 refs.